Technical Efficiency Analysis of Maize Farmers in the Eastern Region of Ghana - M., John K.; ., Wayo Seini (Journal of Social and Development Sciences, 2013)
This study assesses the technical efficiency and its determinants of maize farmers in the Eastern Region of Ghana. A multi stage random sampling procedure was employed to select 226 maize farmers from the four main geographical areas of the region for the study. A well-structured questionnaire and field observations were employed to collect relevant information from the respondents. Data collected was analyzed using relevant econometric techniques. The results indicate that elasticities of mean output for agrochemicals, hired labor, other inputs are positive while those of seed, fertilizer and family labor are negative. The computed return to scale on the other hand reveals that, on average, the maize farms exhibit decreasing returns to scale. The joint effect of operational and farm-specific factors influence technical efficiency but individual effects of some variables are not significant. Mean technical efficiency level of the farmers is estimated to be 51%, indicating that the possibility of increasing maize production in the region given the current state of technology and inputs level can be achieved in the short run by increasing the technical efficiency level of the farmers by 49% through the adoption of practices of the best maize farmer. Further, the empirical results from the inefficiency model show that extension visit, FBO membership, frequency of meeting by members of FBOs, formal training in maize farming, cash and in-kind credits are the major determinants of the farmers’ technical efficiency level. Finally, the resource use efficiency results revealed that agro-chemicals and hired labor are under-utilized whereas seed, fertilizer and family labor are over-utilized by maize farmers in the region. These results have implications for management of small and medium scale food crop farms in developing countries.